Risk Factors in Start-Ups: An Evaluation - Neilan Soylu; Mustafa Halid Karaarslan (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Start-ups are considered as the way to ensure high added value and competitiveness in economies around the world. While investments in start-ups and government incentives tend to increase, evaluation of start-ups risks is an important issue not only for increasing the return on the investment but also for the efficient use of resources. This study examines the specific risks of 23 start-ups operating in various sectors in Türkiye. Employing multiple case method, the start-ups’ risk factors have been analyzed under four major dimensions (organization and human capital; technology and product; financials; marketing and implementation). Factors affecting the risk of start-ups have been assessed in depth according to their expected impact on funders’ decisions. Findings reveal that issues like key personnel dependence and process efficiency must be carefully assessed as they have a critical role in the survival of start-ups. Due to lack of financial resources and the length of time needed to reach a positive cash flow, the start-ups’ focus can be frequently shifted from their core operations to temporary income generating activities, which also increases the risk. Start-ups are set up subsequently to successfully completed R D projects, therefore their founders mostly have an engineering background. However, although high R D potential can be considered as having a risk decreasing effect, it is still their ability to efficiently manage financial resources and to adopt an appropriate marketing strategy to commercialize their products in order to generate cash flows and to attain a stable growth that actually determines their risk levels.